Effects of valence band tails on the blue and red spectral shifts observed in the temperature‐dependent photoluminescence of InN. Issue 8 (22nd March 2013) - Seetoh, Ian P.; Soh, Chew Beng; Fitzgerald, Eugene A.; Chua, Soo Jin
Abstract Lineshape‐fitting, using a model that takes into account of band tails, was performed on the photoluminescence spectra measured from InN samples at temperatures varying from 5 to 300 K. By analyzing how the fitted parameters varied with temperature, it was found that the previously observed blue and then red shift of emission peak position with increasing temperature is related to valence band tails. The initial blue‐shift at low temperature is due to filling of valence band tails while the subsequent Varshni red‐shift is due to lattice expansion. In a series of samples grown using increasing trimethylindium flow rates during metal organic chemical vapor deposition, the impurity potential that describes the width of the valence band tail increased from 18 to 26 meV, possibly due to more nitrogen vacancies being created in the material.